2017
DOI: 10.3390/ijms18081637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin on Early Pregnancy in Mouse: Involving the Regulation of StAR, Cyp11a1, and Ihh Expression

Abstract: To test whether melatonin plays an important role in the process of early pregnancy, melatonin was given in drinking water to pregnant mice at different gestation stages. These included mice who were given melatonin 14 days prior to their successful mating (confirmed by vaginal plug) (Group A), after successful mating (Group B), and 14 days prior to and until after successful mating (Group C). Melatonin administration significantly enhanced serum as well as ovarian melatonin levels in the mice. It was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Melatonin is produced within the retina and is known to stimulate sirtuin activity in mitochondria, which deacetylates many of the enzymes involved within the TCA cycle. Previous studies have shown that supplementation with melatonin has no known toxicity affects when taken during pregnancy in both humans and mice [79][80][81]. Additionally, resveratrol is a plant-derived polyphenol that has been widely studied for its potential benefits as a protective agent against cancers, mutagenesis, and a variety of other biological functions [81].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is produced within the retina and is known to stimulate sirtuin activity in mitochondria, which deacetylates many of the enzymes involved within the TCA cycle. Previous studies have shown that supplementation with melatonin has no known toxicity affects when taken during pregnancy in both humans and mice [79][80][81]. Additionally, resveratrol is a plant-derived polyphenol that has been widely studied for its potential benefits as a protective agent against cancers, mutagenesis, and a variety of other biological functions [81].…”
Section: Discussionmentioning
confidence: 99%
“…In general terms, reproductive disorders triggered through hormonal alterations represent one of the main causes of infertility [ 20 ]; this is why many studies have been focused on understanding melatonin functions during pregnancy [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin seems to improve uterine receptivity and embryo implantation in early pregnancy by stimulating the development of the corpus luteum before gestation. A recent study by Guan et al [63] demonstrated that melatonin given orally to mice for 14 days prior to mating was essential to improve implantation by lowering E2 secretion while upregulating the P4-regulated Indian Hedgehog (Ihh) factor expression in the endometrium on day 7.5 of gestation. After successful mating, melatonin treatment for 14 days increased P4 secretion and promoted enhanced expression of LIF.…”
Section: Figurementioning
confidence: 99%